EFFECT OF PARENTAL HARMONY ON ADOLESCENTS SEXUAL RISK BEHAVIOUR IN URBAN AREAS OF INDONESIA - Suparmi Suparmi (Pusbindiklat - LIPI, 2015)
Adolescents are at high risk for a number of negative health consequences associated with early and unsafesexual activity. This study is aimed to analyze the effect of parental harmony on adolescents sexual risk behaviourin urban areas. There were 1,491 adolescents entered into the analysis. The result shows that adolescents whohad good parental harmony relationship accounted for 66% of the reduction to had sexual risk behaviour ratherthan those who did not. Adolescents who had juvenile delinquency increased 3.2-fold to had sexual risk behaviourrather than who did not. Main policy implication of this finding is the importance of parental harmony relationshipto reduce adolescents sexual risk behaviour.